Isolation, diversity, and antimicrobial activity of fungal endophytes from Rohdea chinensis (Baker) N.Tanaka (synonym Tupistra chinensis Baker) of Qinling Mountains, China - Chao An; Saijian Ma; Xinwei Shi; Wenjiao Xue; Chen Liu; Hao Ding (PeerJ, 2020)
Endophytic fungi have been emerged as fruitful resources for producing structurally fascinating and biologically active secondary metabolites. However, endophytic fungi from medicinal plants of Qinling Mountains–the most important natural climatic boundary between the subtropical and warm temperate zones of China with an astonishingly high level of biodiversity–have rarely been explored as potential sources of novel fungal species and active secondary metabolites. In this study, a total of 371 fungal colonies were successfully isolated from 510 tissue segments of the medicinal Tupistra chinensis Baker collected from Qinling Mountains, China. Roots of T. chinensis Baker are used as a folk medicine to ameliorate pharyngitis and treat rheumatic diseases. A total of 100 representative morphotype strains were identified according to ITS rDNA sequence analyses and were grouped into three phyla (Ascomycota, Basidiomycota, Mucoromycota), seven classes (Dothideomycetes, Sordariomycetes, Eurotiomycetes, Microbotryomycetes, Agaricomycetes, Leotiomycetes, Mortierellomycetes), and at least 35 genera. The genera of Collectotrichum (IF, 29.92%), Fusarium (IF, 8.36%), Aspergillus (IF, 8.09%), and Dactylonectria (IF, 5.39%) were most frequently isolated from the tissues of T. chinensis Baker. The Species Richness Index (S, 65) and the Shannon-Wiener Index (H′, 3.7914) indicated that T. chinensis Baker harbored abundant fungal resources. Moreover, five isolates were potential new taxa because of low similarity of ITS sequences ranged from 95.09%∼96.61%. Fifteen out of 100 endophytic fungal ethyl acetate extracts exhibited inhibitory activities against at least one pathogenic bacterium or fungus. Two important lead compounds produced by two stains (F8047 and F8075) with high antimicrobial activities were identified using high performance liquid chromatography (HPLC) and ultra-performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC–QTOF MS) analyses. In addition, it was noteworthy that the strain F8001, which may be a potential new species, showed antimicrobial activity and should be investigated further. Overall, these results indicated that the endophytic fungi from T. chinensis Baker could be exploited as a novel source of bioactive compounds.